It works out that the solutions are: x = 3 and y = 2
It works out that: x = 3 and y = 2
Add 3 to 46 then divide by 7.
3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y
Add the two equations and get 4x = 12 so x = 3 and y = -1
8x-1 = 7x+2 Add 1 to both sides: 8x = 7x+3 Subtract 7x from both sides: 1x = 3 ie x = 3
-7x - 2y = -3
7Y = 33-4Y ( add 4Y to both sides of equation ) 11Y = 33 ( divide both sides of equation by 11 ) Y = 3
4y/4 = 3/4 y = 3/4
2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7
The answer to the math problem -3 7x plus 7 is x equals 1/3.
Subtract by 7x and divide by 2.
7x-3=39 7x=42 x=6
If: 3x-3 = 7x+21 Then: x = -6
The standard form is 7x + 2y - 3 = 0
4y + 10 = 22 4y - 10 - 10 4y=12 4y 4y 4y=3
7x - 3 = 3 Subtract 3 from both sides: 7x - 6 = 0 So a = 7 and b = -6
its pretty easy: 3-2 = 1 so if u multiply 1 x 7x, it equals 7x
4y + 19 = 74y = 7-194y = -124y/4 = -12/4y = -3
A1: 7x-4y=9 , 3x+2y=15 and 7x-4y=9, 6x+4y=30 so 13x=39 x=3 now plug it in for y 9+2y=15 so y=3 A2: The right expression is missing a + or - between the 3x and 2y. For the purpose of this demo, let's assume it is 3x+2y-15. It can be solved by multiplying the right expression by 2, then add the expressions. That will eliminate y. Then solve for x. When x is known, plug its value into either of the expressions and solve for y. To start: 2(3x+2y-15)=6x+4y-30 adding the two (7x-4y-9)+(6x+4y-30)=13x+0y-39=13x-39 solve for x